PENGGUNAAN MEDIA PUHI (POP UP HISTORY OF INDONESIA) MELALUI METODE MAKE A MATCH PADA MATERI SEJARAH PENINGGALAN KERAJAAN ISLAM DI INDONESIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Hanifah, Nurdinah; Irawati, Riana; Rohtiana, Safa’ah Nuraini (Jurnal Pena Ilmiah, 2017)
The purpose of this research is to improve student learning result of fifth grade students ofÂ SDN Talun with implementation of PUHI (Pop Up History of Indonesia) with Make a Match method. The form of this research was class action research. The research performed in three cycles, each cycle has four, each cycle cincist planing, implementing, observation, and reflection. The subjects of this research wereÂ the fifth grade students of SDN Talun which consist of 25 students. The techniques of collecting data in this research are interview, observation, tests, and field notes. Data processing techniques used are data processing techniques and data processing techniques results. The validation of data used is member check, triangulation, and audit trail. The conclusion of this research is implementation of PUHI (Pop Up History of Indonesia) with Make a Match method can improve the learning outcomes of fifth grade students of SDN Talun.